Perkembangan. Ilmu Hukum dalam Perspektif Perkembangan Sains Global - Zudan Arif Fakrulloh (Jurnal Hukum IUS QUIA IUSTUM, 1999)
The impact of global science on the development of legal science has been the normative reduction or positivization of law. This leads to streng the ning the normative image of law, narrowing the appearance of law, sparating law from the social facts, etc. The seimply that a new theory capable of deliberating of law from its normative of image issuch urgent that the theory is capable of describing the truth about law. There fore, Critical Legal Studiesshould begiven a conducive room to deveiop in order to enlighten the legal science.